Motivational Influences and Challenges in Quranic Recitation Proficiency: A Study Among Islamic Educational Teacher Training Department State Islamic University Ar-Raniry Banda Aceh Students - Munzir, Munzir (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2023)
This study delves into the complex dynamics of Quranic recitation proficiency among students in the Islamic Educational Teacher Training Department at State Islamic University Ar-Raniry, Banda Aceh. Through surveys, interviews, and discussions, the research explores motivational factors, challenges faced, and the relationship between teaching methods and proficiency, and proposes strategies for enhancement. The findings emphasize the importance of understanding intrinsic and extrinsic motivations, addressing challenges hindering proficiency, and adopting interactive and culturally sensitive teaching methods. By integrating personalized learning approaches, teacher training programs, and community engagement initiatives, this study provides valuable insights for optimizing Quranic education, fostering motivation, and nurturing a deep connection with religious heritage.